A Family of Fifth-Order Iterative Methods for Solving Nonlinear Equations (Communications in Mathematical Research, 2021)
In this paper, we present and analyze a family of fifth-order iterativemethods free from second derivative for solving nonlinear equations. It is establishedthat the family of iterative methods has convergence order five. Numerical examplesshow that the new methods are comparable with the well known existing methodsand give better results in many aspects.
Keywords: Newton's method; iterative method; nonlinear equation; order of convergence.